1998
DOI: 10.1139/x97-207
|View full text |Cite
|
Sign up to set email alerts
|

Biomass partitioning and nitrogen retranslocation in black spruce seedlings on competitive mixedwood sites: a bioassay study

Abstract: Black spruce (Picea mariana (Mill.) BSP) seedlings were exponentially nutrient loaded by applying 3 or 6 times more fertilizer than recommended for conventional seedling production in the nursery. Loaded seedlings were similar in height and biomass to nonloaded seedlings after nursery culture, but their tissue N, P, and K content was almost twice as much as that of nonloaded seedlings. The seedlings were transplanted on intact potted substrates (bioassays) retrieved with natural vegetation from two boreal mixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 27 publications
6
37
0
Order By: Relevance
“…Excess fertilization (e) may induce toxicity, often indicated by decreased plant growth and N content but elevated tissue nutrient concentration. Such higher internal nutrient reserves acquired during nutrient loading have been shown to correlate well with improved field performance of tree seedlings (Salifu and Timmer 2003b;Malik and Timmer 1998). This simple model has been used to adapt the concept of steady-state nutrition to soilbased seedling culture by developing fertilizer delivery models which effectively induce steady state nutrition (Marney et al 2010) …”
Section: Wwwintechopencommentioning
confidence: 97%
See 1 more Smart Citation
“…Excess fertilization (e) may induce toxicity, often indicated by decreased plant growth and N content but elevated tissue nutrient concentration. Such higher internal nutrient reserves acquired during nutrient loading have been shown to correlate well with improved field performance of tree seedlings (Salifu and Timmer 2003b;Malik and Timmer 1998). This simple model has been used to adapt the concept of steady-state nutrition to soilbased seedling culture by developing fertilizer delivery models which effectively induce steady state nutrition (Marney et al 2010) …”
Section: Wwwintechopencommentioning
confidence: 97%
“…2) probably because of retranslocation to the leaves. Malik and Timmer (1998) also used this diagnostic approach to study nutrient retranslocation in nutrient loaded and non-loaded black spruce seedlings planted on competitive boreal mixedwood forest sites. Thus, vector diagnosis approach can be used to study effects of different management regimes on both plant nutrient allocation and retranslocation processes.…”
Section: Nutrient Allocation Patternsmentioning
confidence: 99%
“…Excess fertilization (e) may induce toxicity, often indicated by decreased plant growth and N content but elevated tissue N concentration. Higher internal nutrient reserves acquired during nutrient loading have correlated well with improved field performance of seedlings [28,37].…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies manipulating nutrients and water levels have shown that increased height, diameter, and volume production were the result of improved production of photosynthates generated by greatly increased leaf area due to the establishment of non-limiting conditions based on irrigation and fertilization (Albaugh et al, 2004;Bergh et al, 1999). Past studies focused on the new growth of established trees, and the response occurred mainly in new shoots leading to the proposition that this was a reflection of withdrawal and retranslocation of resources to sinks of new growth (Malik and Timmer, 1998;McAlister and Timmer, 1998;Xu and Timmer, 1999). However, these processes studied under field conditions and on the new growth of established trees are not necessarily applicable to first or second year transplants, or containerized plants.…”
Section: Effect Of Resource Availability On Growthmentioning
confidence: 99%